A world class university: UiTM in focus / Mas Anom Abdul Rashid and Mohd Noor Azman Othman - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman (2006)
Globalisation does not only pressure manufacturers to produce better products but, also institution of higher learning to produce better graduates who are of global standards and able to become global players in the future. The needs to produce higher quality graduates also lead institutions around the world wanting to be recognised as World Class University (WCU). This paper discusses the general view of a world class university and its characteristics. At the end it touches on UiTM preparation of becoming a WCU.